ANALISIS PEMAHAMAN KONSEP IPA PADA MASA COVID-19 DI SDN KALANGANYAR - Rifdah Ayu Fajri; Fitria Wulandari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Natural science learning in elementary school is fundamentally learning that directs students to see the facts, concepts, and theories regarding the universe. The Covid-19 pandemic has caused the implementation of the natural science learning process and had to be applied to online learning. This student’s learning difficulty is an important issue to understand the concept of natural science learning. The teacher is required to be able to know and identify the students' conceptual understanding of natural science learning. The research in this article is aimed to describe the conceptual understanding and factors on the material of temperature and heat in natural science learning. The research was conducted at SDN Kalanganyar Sedati. The type of research is qualitative research. The research methods used were tests, interviews, and documentation. Based on the results, the analysis of the conceptual understanding of natural science learning showed that 37.5% of students did not understand concepts enough, 50% of students who understood the concepts, and 12.5% of students who really understood the concepts in natural science learning. In conclusion, many students still did not understand the concept of natural science learning because the learning process was conducted online. Therefore, the students did not understand the learning material a lot presented by the teacher.